2012
DOI: 10.1002/ep.11698
|View full text |Cite
|
Sign up to set email alerts
|

A process for the selective removal of arsenic from contaminated water using acetate functionalized zinc oxide nanomaterials

Abstract: This research article deals with the uptake of arsenic from contaminated water using acetate functionalized zinc oxide (ZnO) nanomaterials. The ZnO nanomaterials of various sizes (6–60 nm) have been synthesized following different wet chemical routes. The arsenic removal efficacy of acetate functionalized ZnO nanomaterials was carried out at different pH and time interval. It has been concluded from the study that ZnO nanomaterials (<60 nm) prepared by zinc acetate precursor effectively removes arsenic, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…S3 proves that ZnO NPs can adsorb As in nutrient solution and decrease the amount of As available in nutrient solution. Other studies have also demonstrated ZnO NPs were used for adsorption and removal of As in water (Lata and Samadder 2016;Singh et al 2013). Previous study showed that the adsorption of As on CeO 2 NPs significantly increased the hydrodynamic size of it and induced greater precipitation of CeO2 NPs-As complex (Conway et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…S3 proves that ZnO NPs can adsorb As in nutrient solution and decrease the amount of As available in nutrient solution. Other studies have also demonstrated ZnO NPs were used for adsorption and removal of As in water (Lata and Samadder 2016;Singh et al 2013). Previous study showed that the adsorption of As on CeO 2 NPs significantly increased the hydrodynamic size of it and induced greater precipitation of CeO2 NPs-As complex (Conway et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nanocrystalline titanium dioxide [22,23], acetate functionalized zinc oxide [24], zinc oxide in combination with Fe 2 O 3 and TiO 2 [25] and other metal oxides have been developed for effective removal of arsenic [26].…”
Section: O 4 )mentioning
confidence: 99%
“…Therefore, different procedures, such as ion exchange, adsorption, precipitation, and membrane techniques have been studied for AS removal from aqueous solutions, among which, adsorption technique is more popular and practical, cost-effective, easy to use, which has a good efficiency (1)(2)(3). Different adsorbents have been studied for As removal, such as hydroxides and oxides of iron(III) (1,(3)(4)(5), hydroxides and oxides of aluminum (1,6), activated carbon (7), chitosan (8,9), activated alumina (10), zinc oxide (1,11), biosorbent (9,12), layered double hydroxides (LDH s ) (13)(14)(15)(16)(17)(18)(19), and magnetic Fe 3 O 4 -graphene (20). LDHs are known as inorganic compounds which have a structure similar to clays.…”
Section: Introductionmentioning
confidence: 99%